Comprehensive Management model for increasing the competitiveness of small and medium artisan jewelry enterprises in Peru - Mejia-Pajuelo, K. (2020)
Today, many small and medium enterprises (SMEs) either go out of business or see their growth being stalled due to poor activity management and organization, which is why they are often unprepared to engage against large companies leading their competitive markets. This study aims to develop a comprehensive management model, exclusively designed for SMEs in the jewellery sector, which may encompass all areas that create value and make them competitive. The development of this comprehensive management model was deployed in 21 steps classified into three tiers based on three major philosophies. This study uses lean manufacturing to identify activities that add value and reduce waste, and lean green was used to provide the environmental care and culture approach required for a friendly and fair workplace environment. The selected scenario is a jewelry workshop, wherein techniques and tools were completely applied and yielded a 20% increase in operating performance and a 15% increase in annual return.